Case report: Bevacizumab-induced cerebrovascular events: a case series report and literature review - Chen, Ke; Jiang, Boyang; Yan, Huiping; Yang, Liu; Chen, Zheling (Frontiers in Oncology, 2025)
In clinical use, bevacizumab has improved the overall survival (OS) and progression-free survival (PFS) of malignant solid tumors, and the safe use of bevacizumab has gradually become the mainstream direction of clinical, nursing and pharmaceutical research. Bevacizumab is a humanized anti-VEGF drug. By binding to VEGF, it loses the opportunity to activate VEGFR and then plays an anti-angiogenic role. In addition, more and more studies have emphasized the efficacy and safety of bevacizumab in the treatment of brain metastases from solid tumors. Bevacizumab has its advantages in terms of crossing the blood-brain barrier, increasing radiosensitivity, and reducing radiation-induced brain edema. However, VEGF can maintain the normal function of vascular endothelial cells. Blocking the VEGF pathway can lead to endothelial dysfunction, and the anti-VEGF mechanism of bevacizumab will inevitably lead to a series of thrombotic events and bleeding events. This study reported six cases of cerebrovascular accidents, including ischemic stroke and cerebral hemorrhage, after bevacizumab use. At the same time, this study reviewed the related studies of cardiovascular and cerebrovascular accidents caused by bevacizumab, and analyzed the management of such bevacizumab-related adverse events. We put forward our own views on the early identification and long-term management of adverse events, as well as the subsequent reuse of bevacizumab, hoping to provide more basis for the management of clinical bevacizumab application.